2011
DOI: 10.1111/j.1740-0929.2011.00946.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased intramuscular fat improves both ‘chewiness’ and ‘hardness’ as defined in ISO5492:1992 of beef Longissimus muscle of Holstein × Japanese Black F1 steers

Abstract: It is considered that high-fat beef is more 'tender' than low-fat beef in Japanese consumers. However, 'tenderness' which has been an important beef characteristic, has not been commonly defined. ISO5492:1992 provides internationally established items for sensory texture analysis with simple definitions, and the items classified under 'chewiness' and 'hardness' as defined in the international standard are characterized as useful texture descriptors for beef. The aim of this study was to investigate the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…This result in the current study were in accordance with the former studies, which reported the IMF percentage was improved when dietary protein level was decreased by 3 g/kg [18]. IMF was related to hardness, and the intensities of pork decreased IMF increased in beef [35]. Likewise, restricting dietary CP during the growing pig decreased the firmness and tended to raise the IMF content [36].…”
Section: Meat Qualitysupporting
confidence: 92%
“…This result in the current study were in accordance with the former studies, which reported the IMF percentage was improved when dietary protein level was decreased by 3 g/kg [18]. IMF was related to hardness, and the intensities of pork decreased IMF increased in beef [35]. Likewise, restricting dietary CP during the growing pig decreased the firmness and tended to raise the IMF content [36].…”
Section: Meat Qualitysupporting
confidence: 92%
“…() and Sasaki et al . (), it is generally understood that tender beef is favored by consumers all over the world. Our experiment has revealed that if the amount of marbling alone is increased to make meat tender, then excessive marbling can decrease the important taste characteristics of beef, such as flavor and umami intensity, and result in lower overall evaluation scores.…”
Section: Resultsmentioning
confidence: 99%
“…Beef marbling has been demonstrated to improve both flavor and tenderness, but the degree of the contributions of flavor and tenderness to marbled beef preference has not been established. Consumers independently perceived tenderness and flavor derived from intramuscular fat .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a questionnaire‐based study indicated that most Japanese families preferred soft marbled beef . It was also reported that marbling improves the actual eating qualities of beef such as texture and flavor . Marbling is also an important factor for the quality classification of beef carcasses in the Japanese grading system .…”
Section: Introductionmentioning
confidence: 98%